Evaluation of Performance of Quarry Dust as Additive for Stabilizing Black Cotton Soils - Ismail, Abdussamad (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This paper presents a laboratory investigation into the efficacy of quarry dust as an additive for enhancing the strength characteristics of black cotton soil. Based on the AASHTO classification system and the USCS, the studied soil belongs to A-7-6(12) and CH respectively, implying that the soil is unfit for engineering purposes. The modification of the soil was carried out by treating the soil with 0-30% by weight of quarry dust in 5% increments. Results of compaction tests on the modified soil indicated that, the maximum dry density increases from 1.7 to 1.92 Mg/m3 as the modifier is varied from 0-20%. Conversely, the optimum moisture content decreases from 16 -7.1% for the same variation of the modifier. The CBR value also increases as the amount of quarry dust is increased (from 9 when untreated to 19% when treated with 20% of additive), thus indicating that the additive has the tendency to enhance the strength characteristics of the expansive soil. Based on CBR criterion, the recommended percentage of modifier is 15, being the smallest quantity of quarry dust that satisfies the criteria for a suitable sub-grade cover.